A formação docente e as novas tecnologias no ensino do movimento uniforme variado: uma sequência didática com o software geogebra - Silva, Jando Abraão de Miranda (2018)
The study discusses "The Teacher Training and New Technologies in the Uniformly varied movement Education: a didactic sequence with GeoGebra software". The objectives were to integrate the importance of teacher training and new educational technologies software to high school; present theoretical and practical knowledge of Evenly Miscellaneous Movement (MUV) in its working relations with educational software GeoGebra; articulate the methodological procedures used during teacher training and finally show the applicability of GeoGebra on the activities carried out with teachers of natural sciences, particularly physics. The work was supported in literature and field research that contributed to better clarification on the issue, with qualitative and descriptive nature of approach with the approach the crossing of information in the design of different authors, and bridge the gap between theory and practice. The research presents SADEAM data aligned to the use of GeoGebra software, demonstrating that it is capable of being used in physics lessons planning classes properly during the pedagogical work time (HTP) of teachers of Natural Sciences, motivating teacher physics in the use of the computer lab for application of educational software in physical, favoring the completion of the textbook activities and consequently the learning concepts of MUV. Based on the study, the use of educational software GeoGebra helps to better understand the MUV diagrams teaching to the challenges triggered by the search process and discovery of new, practical and articulated technology to the teacher training process in school locus. In the procedure of teacher training, a teaching guide Physics with GeoGebra software applied to MUV diagrams that serves as a base for exploration activities of the textbook in the school computer lab was established.